Zerumbone disrupts mixed biofilms of Candida albicans and Streptococcus mutans on acrylic resin - Gorayb Pereira, Ana Luíza [UNESP]; Augusto Abreu Pereira, César [UNESP]; Dias, Luana Mendonça [UNESP]; Jorge, Janaína Habib [UNESP]; Pavarina, Ana Cláudia [UNESP] (Taylor & Francis, 2025)
The efficacy of Zerumbone (ZER) against mixed biofilms of fluconazole-resistant Candida albicans (ATCC 96901) and Streptococcus mutans (UA159) was evaluated. Biofilms were cultivated on acrylic resin specimens for 48 h, with alternating supplementation of glucose and sucrose. ZER’s ability to inhibit biofilm formation (pre-treatment) and eradicate mature biofilms (post-treatment) was assessed. Control groups were treated with Chlorhexidine (CHX), Nystatin (NYS), Penicillin (ATB), and distilled water. The efficacy was measured by colony forming units (CFU/mm2) counts, biomass and biofilm’s matrix components quantification (water-soluble polysaccharides [WSP], alkali-soluble polysaccharides [ASPs], proteins, and extracellular DNA [eDNA]). Data were analyzed by one-way ANOVA with Tukey’s or Gammes-Howell post-hoc test for normal data and Kruskal-Wallis test for data that did not meet the assumption of normality (α = 0,05). In the biofilm inhibition assay, ZER decreased total microbiota (C. albicans + S. mutans) (2.7 log10; p < 0.005), C. albicans (1.4 log10; p < 0.038) and S. mutans (1.9 log10; p < 0.048) counting (vs control group), and biofilm components [insoluble proteins: 37% (p < 0.001); WSP: 13% (p < 0.042); ASP: 46% (p < 0.001); eDNA: 11% (p < 0.048)]. Post-treatment with ZER reduced total microbiota (3.2 log10; p < 0.001), C. albicans (3 log10; p < 0.001) and S. mutans (2 log10; p < 0.001) counting (vs control group), and biofilm components [soluble proteins: 20% (p < 0.001); WSP: 20% (p < 0.001); ASP: 51% (p < 0.001); and eDNA: 33% (p < 0.001)]. The positive control groups demonstrated similar or lower efficacy than ZER under all experimental conditions. ZER demonstrates efficacy against mixed biofilms by reducing C. albicans and S. mutans counting and disrupting the extracellular matrix in both assays.
Keywords: biofilm; Candida albicans; extracellular polymeric substance matrix; phytotherapy; Streptococcus mutans